'Underdevelopment' and cheap labour supplies in Southern Rhodesia, 1923-1953 - Keyter, C.F. (My University, 1977)
Any study which seeks to explore the causes of ‘underdevelopment’ in a colonial or ex-colonial territory, is bound to be confronted with the challenge of deciding where capitalism stands in relation to the problem. Stated in unambiguous terms, the basic issue which analysts have been trying to resolve is whether capitalism is fundamentally beneficial or harmful to a developing country.... If we are going to prove, therefore, that capitalism causes underdevelopment, we would need to look at the manner in which modes of production – capitalist and pre-capitalist - interact with one another; how the capitalist mode penetrates into the pre-capitalist mode to form horizontal ties and alliances which maintain the exploitative structure as a whole; and how production in the pre-capitalist is geared and channelled to the advantage of the capitalist....
African Studies Seminar series. Paper presented July 1977
Keywords: Developing countries; Capitalism